Wave Energy Dissipation of Spilling and Plunging Breaking Waves in Spectral Models - Saprykina, Yana; Aydogan, Burak; Ayat, Berna (MDPI, 2022)
On the basis of field experiments and modeling, the dependence of the dissipation of the energy of waves breaking by plunging and spilling on the frequency of wave spectra was investigated. It was shown that the modeling of wave breaking should take into account the compensation of the nonlinear growth of higher wave harmonics, which occurs in different ways for waves breaking with different types and for different methods of modeling a nonlinear source term. The study revealed that spilling breaking waves have a frequency selectivity of energy dissipation at frequencies of second and third harmonics for the Boussinesq and SWAN models for any method of modeling a nonlinear source term. Plunging breaking waves have a quadratic dependence of the dissipation coefficient on frequency in the Boussinesq model and SWAN model with the SPB approximation for a nonlinear source term. The SWAN model with default LTA approximation for plunging breaking waves also assumes frequency-selective energy dissipation. The discrepancy between the LTA default method and others can be explained by the overestimation of the contribution of the second nonlinear harmonic and by inaccurate approximation for the biphase. It is possible to improve the accuracy of LTA and SPB methods by tuning SWAN model coefficients.
Keywords: wave energy dissipation; wave breaking; plunging; spilling; Boussinesq model; SWAN model; wave spectra; spectral modeling; COASTAL ZONE; EVOLUTION-EQUATIONS; TRANSFORMATION; PARAMETRIZATION; PROPAGATION; Engineering; Oceanography